'A tongue tells a thousand truths': narration, translation and illustration in Mohamed Mrabet's Chocolate Creams and Dollars. Issue 3 (4th May 2021) - Sánchez, María Porras; Simour, Lhoussain
ABSTRACT: This study attempts to explore one of the less-studied works in Paul Bowles-Mohamed Mrabet's intellectual and translational collaborations, Chocolate Creams and Dollars, a semi-autobiographical novel illustrated by Philip Taaffe's photographs and found objects. The story presents Driss, a young Moroccan entangled within the shifts and twists of encounter with Westerners in a Northern Moroccan coastal city. By virtue of the three different interventions – Mrabet's story, Bowles's translation and Taaffe's art – the novel is contrapuntal, since each creator presents a different – and often conflicting – point of view. The three of them are observers who record Morocco's 'Interzone' from different angles and cultural agendas. This paper seeks to understand these networks of collaborative connections as they pertain to transcultural contacts, exploring the sexual, cross-cultural, textual and visual discourses running through the narrative fabrics. It analyses Bowles's slippages in authority and in authorship and Taaffe's objectifying and exotifying gaze, and how Driss, Mrabet's protagonist, turns his ethnographic gaze back upon the Westerners. It finally argues that Mrabet's novel, through the symbolic appropriation of experiences with Westerners, articulates intricate discourses on the construction of a cultural identity at the crossroads of neocolonial ventures and postcolonial anxieties.